Effect of graded level Egyptian clover (Trifolium alexandrium) supplementation on in vitro methane production and fermentation pattern - MALIK, P K; SINGHAL, K K; SOREN, N M; THULASI, A; JOSE, L; SANTOSH, S S (The Indian Journal of Animal Sciences, 2013)
Saponin content of Egyptian clover at 3 different cuts was determined and second cut fodder was selected for the supplementation @ 0 (T0), 15 (T1), 30 (T2) and 45 (T3)% to wheat straw based diet to study the effect on in vitro methane production and fermentation pattern. Saponin level of the diet after inclusion of fodder was 0, 0.15, 0.30 and 0.45%, respectively in T0, T1, T2 and T3. Total gas production was significantly higher in T3 and T2 as compared to control group. On the inclusion of clover, a reduction of 9.6, 15.2 and 23.6% in methane production was noticed in T1, T2 and T3, respectively. Decreasing proportion of methane in total gas with increasing levels of supplementation reflected that saponin up to 0.45% of diet did not affect the fermentability adversely. Maximum reduction in protozoal numbers was observed in treatment T3. Significant increase in DM degradability as compared to control was reported in treatment T2 and T3. Likewise TVFA production (mmol/L) also increased considerably on berseem fodder supplementation. Looking at the efficacy of saponin containing Egyptian clover, it may be inferred that there is an urgent need to explore the newer feed resources possessing substantial saponin and to establish their safe inclusion level in diet of ruminants.